Studies at the Faculty of Medicine of the Stefan Batory University in Vilnius 1919–1939 - Przeniosło, Małgorzata (Medical Studies/Studia Medyczne, 2016)
In the article I aimed to examine the conditions and the organisation of the studies at the Faculty of Medicine at the Stefan Batory University (SBU) in Vilnius. Therefore, it became my interest to analyse the functioning of the Faculty and to determine their academic team. Also, it was crucial to define the general rules of study in the interwar period, examine the course of medical and pharmaceutical studies at the SBU, and determine the level of student commitment. The students of the Faculty of Medicine were among the most ‘busy’ at the university. Medical studies were by far the most difficult, both due to the complexity and diversity of theoretical and practical classes, as well as the large number of exams. The studies lasted 16 trimesters, the number of subjects ending in an exam was the highest – 20, and there were 5 subjects which ended in a test.